IMPLEMENTASI PERMENSOS NO 26 TAHUN 2018 TENTANG REHABILITASI SOSIAL ANAK BERHADAPAN HUKUM (ABH) DALAM MEMULIHKAN KEBERFUNGSIAN SOSIAL ABH (Studi Kasus ABH Korban Sebagai Binaan Rehabilitasi Sosial Dinas Sosial Kota Bengkulu) - Ramadhan, Rahmad Andre; Yunilisiah; Tamrin Bangsu (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The high number of problems faced by children facing the law as victims is very important to be considered more conducive and become a common concern in handling. The process of implementing Social Rehabilitation in ABH can determine attitudes and changes in ABH. This study aims to analyze the implementation of Permensos in restoring ABH social functioning. The research method in this study used qualitative methods, informants in this study consisted of 12 informants. Data collection techniques in this study are observation, interviews, and documentation. The results showed that, there are several things that have been in accordance with the provisions of the theory according to Nugroho (2008) and the provisions of the Ministry of Social Affairs, but there are still obstacles and obstacles in implementing the Permensos which include, budget procurement, procurement of infrastructure facilities, and cooperation with other UPTD. In addition, the Social Rehabilitation Process at ABH is still carried out according to the stages and programs available, by looking at the condition of ABH after rehabilitation. The conclusion of this study can be concluded that, the informant has carried out the rehabilitation process in accordance with the provisions of the Ministry of Social Affairs. Social Rehabilitation provided to Children with Legal Conflict aims to enable children to carry out their social functioning which includes the ability to carry out roles, fulfill children's rights, solve problems, self-actualization and development of self-potential, as well as the availability of a social environment that supports the success of children's social rehabilitation.